2017
DOI: 10.1007/s13197-017-2663-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of marine collagen peptides on glucose metabolism and insulin resistance in type 2 diabetic rats

Abstract: The present study was conducted to investigate the effects of marine collagen peptides (MCPs) on glucose metabolism and insulin resistance using a rat model of type 2 diabetes mellitus (T2DM). Forty T2DM obese Wistar rats were randomly assigned to receive varying doses of MCPs or a vehicle control for 4 weeks. Blood glucose and insulin levels, as well as oxidative stress and inflammation were measured. The expression of glucose transporter type 4 (GLUT4) in skeletal muscles and peroxisome proliferator-activate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…As a result, the LCP-fed groups had lower hepatic TG and TC levels, as evidenced by the histological results, demonstrating that hepatic lipid deposits were suppressed. These results are consistent with a previous study showing that collagen peptide derived from chum salmon skin prevented liver steatosis by upregulating PPARα expression in rats [ 32 ]. Our previous study demonstrated the dose-dependent effects of skate skin collagen peptide (without ultrafiltration) on the reduction of the hepatic lipid concentration mediated through the regulation of lipid metabolism-related genes in diet-induced obese mice [ 20 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…As a result, the LCP-fed groups had lower hepatic TG and TC levels, as evidenced by the histological results, demonstrating that hepatic lipid deposits were suppressed. These results are consistent with a previous study showing that collagen peptide derived from chum salmon skin prevented liver steatosis by upregulating PPARα expression in rats [ 32 ]. Our previous study demonstrated the dose-dependent effects of skate skin collagen peptide (without ultrafiltration) on the reduction of the hepatic lipid concentration mediated through the regulation of lipid metabolism-related genes in diet-induced obese mice [ 20 ].…”
Section: Discussionsupporting
confidence: 94%
“…Similarly, the collagen derived from salmon [ 31 ], gray mullet [ 5 ], and skate [ 22 ] exert plasma lipid-lowering effects. In addition, chum salmon skin-derived collagen peptide increases adiponectin and decreases leptin levels in rats [ 32 ]. Similarly, the results of this study indicate that SSCP could have partial effects on regulation of the leptin level, indicating that both LCP and HCP lowers leptin levels.…”
Section: Discussionmentioning
confidence: 99%
“…Salmon protein hydrolysates were shown to stimulate insulin-induced glucose uptake in L6 myocytes (Jin, 2012). Salmon skin gelatin derived peptides were reported to reduce blood glucose concentrations in diabetic rat models through enhancement of circulating GLP-1 concentration and reduction in T2DM-related islet cell apoptosis (Hsieh, Wang, Hung, M.C., & Hsu, 2012;Zhu et al, 2017;Zhu, Peng, Liu, Zhang, & Li, 2010). Salmon protein incorporation into a high-fat, high-sucrose diet was shown to improve whole-body insulin sensitivity and glucose tolerance in male Wistar rats (Pilon et al, 2011).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…These results suggest that MCPs may be a novel therapeutic tools to protect against early cardiovascular complications associated with T2DM. In line with these results, MCPs were found to improve glucose metabolism and insulin resistance, to decrease the expression of oxidative stress biomarkers and inflammatory cytokines and adipocytokines in livers of T2DM rat models [166].…”
Section: Biomedical Applicationsmentioning
confidence: 73%